Enterprise Architecture Framework in Higher Education: Systematic Literature Review - Nur Shabrina Meutia; Endang Sulistiyani; Rizqi Putri Nourma Budiarti; Rita Sari (Universitas Nahdlatul Ulama Surabaya, 2022)
The use of information and communication technology helps improve the quality of education and learning processes, research, libraries and information services, and university management. With the development of ICT, universities are one of the companies engaged in education, so that institutions and universities need an information system planning strategy. This study presents a detailed and extensive systematic literature review (SLR) to select studies that carry out the current application of Enterprise Architecture in higher education. The method used in this research is the incorporation of various systematic literature studies on previous studies related to research objectives. The results of this literature review reveal important aspects related to the use of enterprise architecture applications in higher education, such as the most popular frameworks used in higher education, examine the reasons and determine the criteria for using application-based frameworks, and why enterprise architecture frameworks are needed to implement in higher education.